Wetting and brazing of (HfTaZrNbTi)B2 and (HfTaZrNbTi)C High-Entropy Ceramics by AgCuTi filler - Naser Hosseini; Fabrizio Valenza; Zdeněk Chlup; Sofia Gambaro; Carla Malinverni; Valentina Casalegno; Alexandra Kovalčíková; Monika Tatarková; Ivo Dlouhý; Peter Tatarko (Open Ceramics)
The wetting behaviour of (HfTaZrNbTi)B₂ high entropy boride (HEB) and (HfTaZrNbTi)C high-entropy carbide (HEC) with molten Cu and AgCuTi alloy was investigated via the sessile drop method under an Ar/H2 atmosphere. Pure Cu exhibited non-reactive wetting with contact angles ∼ 120° on HEB and ∼ 126° on HEC. In contrast, AgCuTi alloy showed strong reactive wetting (contact angle ≤ 17°), primarily driven by reactive Ti. The reaction layer was notably thicker for the HEC/AgCuTi system. Due to the better wetting behaviour and high-temperature interactions with the ceramic substrates, AgCuTi alloy was employed as a filler to braze HEB and HEC using pressure-less Field Assisted Sintering Technique (FAST). The resulting joints demonstrated high apparent shear strength of 176 ± 39 MPa for HEC and 116 ± 38 MPa for HEB, exceeding the strength of the base materials in both cases.